THE EFFECT OF DEBT LEVEL, EARNINGS MANAGEMENT, AND CAPITAL INTENSITY ON TAX AGGRESSIVENESS - Herawati Jaenal; Yunita Fitria (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This study aims to test and analyze the effect of debt level, earnings management, and capita; intensity on tax aggressiveness. This study is a type of quantitative research with a population of energy sector companies listed on the Indonesia Stock Exchange (IDX) in the observation period from 2020 to 2023. The sampling technique in this study used a purposive sampling technique which then obtained a research sample of 100 samples. In this study, the data used is secondary data and hypothesis testing uses the regression analysis method with an analysis tool, namely the IBM SPSS Statistics 26 program. The results showed that (1) the level of debt has a negative and significant effect on tax aggressiveness, (2) management has a positive but not significant effect on tax aggressiveness, (3) capital intensity has a positive and significant effect on tax aggressiveness.